2020
DOI: 10.1080/09297049.2020.1740188
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions predict literacy and mathematics achievements: The unique contribution of cognitive flexibility in grades 2, 4, and 6

Abstract: Research has shown that cognitive flexibility plays a critical role in students' learning and academic achievement. However, the unique contribution of cognitive flexibility to academic achievement across schooling is not fully understood. Thus, this study tested whether cognitive flexibility explained a significant amount of variance in academic achievement (i.e., literacy and mathematics outcomes) across Grades 2, 4, and 6, above and beyond fluid intelligence, inhibitory control, working memory, attention, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 87 publications
1
30
2
6
Order By: Relevance
“…Previous research has indicated that cognitive control is involved in a wide range of cognitive activities including learning (Abrahamse et al, 2016), comprehension (Ye and Zhou, 2008), theory of mind (Carlson and Moses, 2001), problem solving (Passolunghi and Siegel, 2001), and general fluid intelligence (Benedek et al, 2014). Moreover, measures of cognitive control have been shown to explain a significant amount of variance in academic achievements, above and beyond the effect of general fluid intelligence (Magalhães et al, 2020). Given these critical aspects, the numbers of studies investigating cognitive control have increased dramatically during the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that cognitive control is involved in a wide range of cognitive activities including learning (Abrahamse et al, 2016), comprehension (Ye and Zhou, 2008), theory of mind (Carlson and Moses, 2001), problem solving (Passolunghi and Siegel, 2001), and general fluid intelligence (Benedek et al, 2014). Moreover, measures of cognitive control have been shown to explain a significant amount of variance in academic achievements, above and beyond the effect of general fluid intelligence (Magalhães et al, 2020). Given these critical aspects, the numbers of studies investigating cognitive control have increased dramatically during the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Reaching school-ages with more robust cognitive shifting skills is important as they represent significant predictors of writing and reading comprehension [ 34 , 35 ] and are related to creativity, that is the ability to generate different responses guided by internal stimuli [ 34 ] and to the ability to quickly adapt behaviors and responses according to different contexts and environmental demands. According to Magalaes and collaborators’ study, cognitive shifting is a unique predictor of academic achievement above and beyond control variables such as working memory, inhibition, fluid intelligence, attention, planning, especially for students after 4 grades [ 36 ]. Moreover, a study conducted by Kertz and collaborators describes as preschoolers with lower cognitive shifting abilities, in comparison to children with high shifting skills balanced for gender, parental education, IQ and severity symptoms at preschool age, showed greater depression and anxiety symptoms in the school years [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pawar (2020) Pawar ( 2020) (Best, Miller, & Naglieri, 2011;Fuhs, Nesbitt, Farran, & Dong, 2014;St Clair-Thompson & Gathercole, 2006;Thorell, Veleiro, Siu and Mohammadi, 2013) Best et al ( 2011) (Blair & Razza, 2007;Filipe, et al, 2020;Schmitt, McClelland, Tominey, & Acock, 2015;Tominey & McClelland, 2011) Thorell et al (2013) Bull, Espy and Wiebe ( 2008) (LeFevre, et al, 2010;Purpura, et al, 2017) (Clark, et al, 2010) (Pawar, 2020) . (Homer, Plass, Raffaele, Ober, & Ali, 2018;Parong, Mayer, Fiorella, MacNamara, Homer, & Plass 2017;Nouchi et al, 2012) (Holm, et al, 2018;Magalhães, et al, 2020;Toll, et al, 2011;Wang, et al, 2012) Cognitive Flexibility Attentional System Inhibitory Control (Blair & Razza, 2007;Bull et al, 1999;Bull & Scerif, 2001 (Clark, et al, 2010) . (Geary, et al, 2008) Tower of Hanoi Tower of London (Welsh, & Huizinga, 2001) Tower of Hanoi (Humes, et al, 1997;Welsh, & Huizinga, 2001) Jigsaw Puzzle (Chin, 2009) (Miyake et al, 2000;Toll, et al, 2011) (Burgess, et al, ...…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…(Davidson, Amso, Anderson & Diamond, 2006) . Shahrivar, Doost, Khademi, & Nejad, 2015) test-retest reliability (Gioia et al, 2000;Zarrabi et al, 2015) Convergent validity (Gioia et al, 2000) Divergent validity (Gioia et al, 2000) ( Gioia et al, 2000) (Esplin, et al, 2020Kirk, et al, 2017) (Holm, et al, 2018;Magalhães, et al, 2020;Wang, Tasi, & Yang, 2012) Spaulding, (2017, 1998) . .…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
See 1 more Smart Citation